Translating the Brazilian Dietary Guidelines into clinical practice: innovative strategies for healthcare professionals - Vanessa Del Castillo Silva Couto; Maria Laura da Costa Louzada; Patrícia Constante Jaime (Archives of Endocrinology and Metabolism)
ABSTRACT TheBrazilian Dietary Guidelines provide crucial recommendations for a healthy diet, aiming at promoting health and preventing non-communicable chronic diseases. The core principle is the preference for natural or minimally processed foods and freshly prepared dishes over ultra-processed foods. Despite their growing recognition, healthcare professionals struggle to integrate these guidelines into clinical practice. This article aims to present two innovative strategies for incorporating the Brazilian Dietary Guidelines into healthcare. The Protocols based on the Brazilian Dietary Guidelines for Individual Dietary Advice are standardized clinical tools to support healthcare professionals (nutritionists or not) in giving nutritional advice during individual appointments to various life stages. The Protocols operationalize the assessment of individuals’ dietary patterns using the Food Consumption Markers Questionnaire and support the delivery of personalized and priority recommendations through a stepwise flowchart. Conversely, Brazilian Dietary Guidelines-based Meal Plans consist of personalized dietary prescriptions comprising structured daily menus that, unlike conventional plans primarily focusing on nutrient goals, prioritize overall eating patterns guided by the Brazilian Dietary Guidelines. The proposal encourages, in the first place, the selection of a variety of culinary preparations based on natural or minimally processed foods, emphasizing tasteful, accessible, and culturally appropriate choices as the initial step. In a second step, these plans can be customized to individual energy requirements, and adjustments made based on strategic nutrient needs. This article aims to support the enhancement of healthcare professionals’ skills in promoting healthy eating practices, thereby contributing to improved health and a reduced disease burden among the Brazilian population.